Mobile application for behavioral risk management associated with cryptocurrency investing - Korotov, Nikita (2025)
This thesis investigates the influence of behavioural economic biases on decision-making in cryptocurrency trading. Drawing on established theories from behavioural finance, specifically Prospect Theory, developed by Nobel laureate Daniel Kahneman and Amos Tversky, it identifies how various cognitive biases and heuristics, such as overconfidence, availability heuristics and loss aversion, impact decision-making under uncertainty. These theoretical foundations are directly applied to the context of cryptocurrency trading. To mitigate irrational decision-making, a mobile application was designed and developed to detect and mitigate behavioural biases in real time. The app was evaluated through user testing and thematic analysis, with findings indicating that the system reliably identifies key biases and provides meaningful feedback. However, challenges remain regarding beginner accessibility, coverage of additional biases, and internal security mechanisms. The study concludes by outlining areas for future development, including enhanced user onboarding, expanded feature sets, integration of additional bias detection, and the potential use of AI-driven algorithms for personalised interventions. The results demonstrate the practical value of behavioural economics in supporting safer and more rational participation in cryptocurrency trading.